Silicon-carbon negative electrode material and preparation method thereof
Through the three-dimensional conductive framework structure design of porous silicon particles, gradient carbon layer and carbon nanotubes, the structural damage and insufficient conductivity of silicon carbon anode materials in lithium-ion batteries due to volume expansion are solved, and high cycle stability and rate performance are improved.
Patent Information
- Application Number
- CN202510667032.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-22
- Publication Date
- 2025-07-11
AI Technical Summary
The existing silicon-carbon anode materials in lithium-ion batteries have structural damage, conductive network fracture and electrochemical performance decay due to volume expansion, and insufficient cyclic stability and rate performance.
The three-dimensional conductive framework structure design of porous silicon particles, gradient carbon layer and carbon nanotubes is designed to form a stable three-dimensional conductive network through ball milling. The inner hard carbon layer and the outer soft carbon layer provide structural support and flexibility. The carbon nanotubes build an efficient electron transmission network.
It significantly improves the cycle stability and rate performance of silicon carbon negative electrode materials, maintains high specific capacity, solves the problem of easy structure collapse and weak interface combination, and improves the overall performance of the battery.
Smart Images

Figure CN120300167A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of lithium-ion technology, and particularly to a silicon-carbon anode material and a preparation method thereof. Background Art
[0002] Silicon is currently the anode material with the largest theoretical capacity, with a specific capacity of up to 4200 mAh / g, far higher than the theoretical capacity of graphite (the theoretical capacity of graphite anode material is only 372 mAh / g). Moreover, silicon has the advantages of low lithium potential and low cost, and is expected to replace graphite as the anode material for the next generation of lithium-ion batteries. However, as an anode material, silicon undergoes severe volume expansion and contraction during the lithium intercalation process, resulting in easy pulverization of the material, detachment from the current collector, and loss of electrochemical performance.
[0003] Due to the structural stability of carbon materials, their volume change is relatively small during charge and discharge, with good cycle stability, and they are chemically similar to silicon. Therefore, silicon and carbon are often compounded to improve the volume expansion effect of silicon and enhance its electrochemical stability. However, when lithium ions are inserted into the silicon-carbon material (Li-Si alloying), the volume expansion can reach 300%-400%, and it shrinks during deintercalation. After repeated charge and discharge, it is difficult for the silicon-carbon material to solely inhibit the volume expansion of silicon, resulting in the rupture and pulverization of silicon particles, loss of electrical contact; the collapse of the electrode structure, continuous consumption of the electrolyte (repeated rupture and regeneration of the SEI film); the detachment of the active material from the current collector, and a sharp increase in internal resistance, leading to problems such as weak interfacial bonding, insufficient conductivity, and easy collapse of the silicon-carbon composite material. This directly affects the electrochemical performance and battery life of the battery material.
[0004] Chinese patent document with application publication number CN202410253165.3 discloses a preparation method of a silicon-carbon anode material. In this method, silicon dioxide powder and metal powder are ball-milled and mixed, then heated for a thermite reaction, and the obtained material powder is placed in a gas atmosphere containing carbon dioxide for reduction treatment, and then the obtained product is pickled, filtered by suction, and dried to obtain a Si / C nanocomposite material; the nanoscale Si / C is combined together, and this material exhibits abnormal lithium storage capacity, good conductivity, excellent rate performance, and cycle stability, thus improving the cycle performance and rate performance of the anode material.
[0005] US patent document with patent number US20230219819A1 discloses a preparation method of a silicon-carbon composite material. This scheme uses chemical vapor deposition (CVD) to coat a carbon layer to obtain a uniform silicon-carbon composite material, which exhibits excellent cycle performance and rate performance.
[0006] While the above two preparation methods improve the silicon-carbon binding ability or conductivity, they also cause structural damage to the silicon-carbon negative electrode, making it not have long-term cycle stability performance and still leading to a decline in cycle stability. Summary of the Invention
[0007] This application aims to at least partly solve one of the above technical problems in the prior art. To this end, the embodiments of this application provide a silicon-carbon negative electrode material and its preparation method, which significantly improve the cycle stability and rate performance while maintaining the high specific capacity advantage of the silicon-based negative electrode.
[0008] A silicon-carbon negative electrode material includes porous silicon particles, a gradient carbon layer, and carbon nanotubes. The gradient carbon layer coats the surface of the porous silicon particles. The gradient carbon layer includes an inner layer of hard carbon and an outer layer of soft carbon. The porous silicon particles and the carbon nanotubes are ball-milled and mixed to form a three-dimensional conductive framework.
[0009] In an optional or preferred embodiment, the pore diameter of the porous silicon particles is 10 - 50 nm, and the porosity is 30 - 60%.
[0010] A preparation method of a silicon-carbon negative electrode material for preparing any one of the above silicon-carbon negative electrode materials, characterized by including the following steps: Step 1, fabricate porous silicon; Step 2, mix the porous silicon with phenolic resin and perform staged carbonization in an inert atmosphere; Step 3, ball-mill and mix the carbonized porous silicon with carbon nanotubes to form a three-dimensional conductive framework.
[0011] In an optional or preferred embodiment, during the carbonization process, keep the temperature at 300 °C for 2 h in the first stage and at 800 °C for 5 h in the second stage.
[0012] In an optional or preferred embodiment, in the said Step 3, the mass ratio of the carbon nanotubes is 5 - 10%.
[0013] In an optional or preferred embodiment, in the said Step 2, the porous silicon and the phenolic resin are mixed in a mass ratio of 1:2.
[0014] In an optional or preferred embodiment, fabricating porous silicon includes the following steps: Ultrasonically clean the single-crystal silicon wafer successively with acetone, ethanol, and deionized water to remove surface contaminants; Sputter a 5 - 10 nm layer of silver nanoparticles on the surface of the single-crystal silicon wafer as a catalyst, then immerse the single-crystal silicon wafer in a mixed solution of hydrofluoric acid and hydrogen peroxide, etch at room temperature for 30 minutes, and finally remove the residual silver particles with nitric acid, and obtain porous silicon after cleaning and drying.
[0015] In an optional or preferred embodiment, fabricating porous silicon includes the following steps: Using silicon dioxide as a template and impregnating it in silane gas; Depositing silicon at 400 °C to fill the pores of the silicon dioxide template; Etching the silicon dioxide template with hydrofluoric acid to obtain porous silicon with a reverse replica template.
[0016] In an optional or preferred embodiment, fabricating porous silicon includes the following steps: Mixing hydrofluoric acid and ethanol in a volume ratio of 1:1; Using a single-crystalline silicon wafer as the anode and a platinum sheet as the cathode, etching for 20 minutes at a current density of 10 mA / cm², washing with deionized water and drying to obtain porous silicon.
[0017] In an optional or preferred embodiment, 1% LiF is added as an SEI film modifier for prelithiation treatment to compensate for the first-cycle capacity loss.
[0018] Based on the above technical solutions, the embodiments of the present application have at least the following beneficial effects: Through the collaborative design of the three-dimensional conductive framework of porous silicon particles, gradient carbon layers, and carbon nanotubes, the present invention successfully solves the problems of weak interfacial bonding, insufficient conductivity, and easy structural collapse existing in existing silicon-carbon anode materials. While maintaining the high specific capacity advantage of silicon-based anodes, this material significantly improves the cycle stability and rate performance. Description of the Drawings
[0019] The following further illustrates the present application in conjunction with the drawings and embodiments; Figure 1 is the first Coulomb efficiency of the silicon-carbon anode material and the traditional carbon anode material in the present application; Figure 2 is the relationship diagram between the number of cycles and the retention rate of the silicon-carbon anode material in the present application; Figure 3 The XRD of the silicon-carbon anode material in the present application confirms the absence of free silicon oxide phase diagram. Detailed Embodiments
[0020] To make the above objects, features, and advantages of the present application more obvious and understandable, the following provides a detailed description of the specific embodiments of the present application in conjunction with the drawings. Many specific details are set forth in the following description to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without departing from the connotation of the present application. Therefore, the present application is not limited by the specific embodiments disclosed below.
[0021] In the description of the present application, it should be understood that the orientation or positional relationships indicated by the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "upper", "lower", "front", "rear", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. are based on the orientation or positional relationships shown in the drawings. These are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and thus should not be construed as a limitation on the present application.
[0022] In addition, the terms "first" and "second" are only used for descriptive purposes and should not be construed as indicating or implying relative importance or implicitly specifying the quantity of the indicated technical features. Thus, features defined with "first" and "second" may explicitly or implicitly include at least one of such features. In the description of the present application, the meaning of "a plurality" is at least two, such as two, three, etc., unless otherwise specifically and clearly defined.
[0023] In the present application, unless otherwise clearly specified and limited, the terms "mounted", "connected", "coupled", "fixed", etc. should be understood in a broad sense. For example, it may be a fixed connection, a detachable connection, or integrated; it may be a mechanical connection or an electrical connection; it may be directly connected or indirectly connected through an intermediate medium, and it may be the internal communication of two elements or the interaction relationship between two elements, unless otherwise clearly limited. For those of ordinary skill in the art, the specific meanings of the above terms in the present application can be understood according to specific circumstances.
[0024] In the present application, unless otherwise clearly specified and limited, the first feature being "on" or "under" the second feature may be that the first and second features are in direct contact, or the first and second features are indirectly in contact through an intermediate medium. Moreover, the first feature being "above", "over" and "on top of" the second feature may be that the first feature is directly above or obliquely above the second feature, or merely indicates that the first feature has a higher horizontal height than the second feature. The first feature being "under", "beneath" and "underneath" the second feature may be that the first feature is directly below or obliquely below the second feature, or merely indicates that the first feature has a lower horizontal height than the second feature.
[0025] It should be noted that when an element is referred to as "fixed to" or "disposed on" another element, it can be directly on the other element or there may also be an intermediate element. When an element is considered to be "connected" to another element, it can be directly connected to the other element or there may be an intermediate element at the same time. The terms "vertical", "horizontal", "upper", "lower", "left", "right" and similar expressions used herein are only for illustrative purposes and do not represent the only implementation.
[0026] Silicon is currently the anode material with the largest theoretical capacity. The specific capacity can reach 4200 mAh / g, which is much higher than the theoretical capacity of graphite (the theoretical capacity of graphite anode material is only 372 mAh / g). Moreover, silicon has the advantages of low lithium potential and low cost, and is expected to replace graphite as the anode material for the next generation of lithium-ion batteries. However, as an anode material, silicon undergoes severe volume expansion and contraction during the processes of lithium insertion and extraction, resulting in the material being prone to pulverization, falling off from the current collector, and losing its electrochemical performance.
[0027] Due to the structural stability of carbon materials, the volume change during charge and discharge is relatively small, and it has good cycle stability. Moreover, since it has similar chemical properties to silicon, silicon is often compounded with carbon to improve the volume expansion effect of silicon and enhance its electrochemical stability. However, when lithium ions are inserted into the silicon-carbon material (Li-Si alloying), the volume expansion can reach 300%-400%. During deintercalation, it contracts. After repeated charge and discharge, it is difficult for the silicon-carbon material to solely inhibit the volume expansion of silicon, resulting in the rupture and pulverization of silicon particles, loss of electrical contact; the collapse of the electrode structure, continuous consumption of the electrolyte (repeated rupture and regeneration of the SEI film); the detachment of the active material from the current collector, and a sharp increase in the internal resistance, leading to problems such as weak interfacial bonding, insufficient conductivity, and easy collapse of the structure in the silicon-carbon composite material. This directly affects the electrochemical performance and battery life of the battery material.
[0028] A Chinese patent document with the application publication number CN202410253165.3 discloses a preparation method for a silicon-carbon anode material. In this method, silicon dioxide powder and metal powder are ball-milled and mixed, then heated for a thermite reaction. After that, the obtained material powder is placed in a gas atmosphere containing carbon dioxide for reduction treatment, and then the resulting product is pickled, filtered by suction, and dried to obtain a Si / C nanocomposite material; the nanoscale Si / C is combined together, and this material exhibits excellent lithium storage capacity, good conductivity, excellent rate performance, and cycle stability, thereby improving the cycle performance and rate performance of the anode material.
[0029] A method for preparing a silicon-carbon composite material is disclosed in the US patent document with the patent number US20230219819A1. This solution uses chemical vapor deposition (CVD) to coat a carbon layer, obtaining a uniform silicon-carbon composite material, which exhibits excellent cycling performance and rate performance.
[0030] While the above two preparation methods improve the silicon-carbon bonding ability or conductivity, they will also cause structural damage to the silicon-carbon negative electrode, making it unable to have long-term cycle stability performance and still resulting in a decline in cycle stability.
[0031] The present invention provides a silicon-carbon negative electrode material and a preparation method thereof. Through the unique three-dimensional conductive framework structure design of porous silicon particles, gradient carbon layers, and carbon nanotubes, the present invention effectively solves the problems of structural damage, conductive network fracture, and electrochemical performance attenuation caused by the volume expansion of silicon materials during the cycling process of existing silicon-carbon negative electrode materials.
[0032] The silicon-carbon negative electrode material of the present invention includes porous silicon particles, gradient carbon layers, and carbon nanotubes. Among them, the surface of the porous silicon particles is coated with a gradient carbon layer, which includes inner-layer hard carbon and outer-layer soft carbon, forming a carbon coating structure with gradually decreasing hardness from the inside to the outside. The porous silicon particles and the carbon nanotubes are mixed by ball milling to form a three-dimensional conductive framework, constructing an efficient electron transport network.
[0033] The porous silicon particles in the present invention have a pore diameter of 10 - 50 nm and a porosity of 30 - 60%. On the one hand, this porous structure provides a large number of diffusion channels for lithium ions, shortens the diffusion path of lithium ions, and accelerates the insertion / extraction speed of lithium ions; on the other hand, the porous structure also provides a buffer space for the volume expansion of silicon materials during the lithiation process, effectively reducing the damage to the material structure caused by volume changes.
[0034] The inner-layer hard carbon of the gradient carbon layer is tightly combined with the porous silicon particles and has high mechanical strength, which can effectively inhibit the volume expansion of silicon materials during charge and discharge; the outer-layer soft carbon has good flexibility and conductivity, can elastically deform when the volume of the silicon material changes, avoid carbon layer cracking, and at the same time maintain good electron conduction performance. This gradient structure with gradually decreasing hardness from the inside to the outside realizes the optimal combination of effective protection of silicon particles and electron transport function.
[0035] Carbon nanotubes play a key role in constructing a three-dimensional conductive network. Through the ball milling process, the carbon nanotubes are fully mixed with the porous silicon particles coated with the gradient carbon layer to form an interconnected three-dimensional conductive framework. This framework structure not only greatly improves the overall conductivity of the material but also provides structural support during the volume expansion and contraction of silicon materials, maintaining the overall structural stability of the electrode material and preventing the active material from detaching from the current collector.
[0036] In one embodiment, the pore size of the porous silicon particles is 20 nm and the porosity is 40%. Such structural parameters enable the porous silicon particles to maintain a high specific surface area and abundant lithium ion transmission channels, while providing sufficient volume expansion buffer space and maintaining the mechanical strength of the material.
[0037] In another embodiment, the pore size of the porous silicon particles is 30 nm and the porosity is 50%. The porous silicon particles under such structural parameters have a larger porosity and can provide more volume expansion buffer space, which is particularly suitable for high-capacity application scenarios.
[0038] The method for preparing the silicon-carbon negative electrode material of the present invention comprises the following steps: Step 1: Making porous silicon. The present invention provides three different methods for making porous silicon, and a suitable process route can be selected according to actual needs.
[0039] Method 1: Ultrasonic cleaning of single crystal silicon wafers with acetone, ethanol, and deionized water in turn to remove surface contaminants; sputtering a layer of 5-10 nm silver nanoparticles on the surface of the single crystal silicon wafer as a catalyst, and then immersing the single crystal silicon wafer in a mixed solution of hydrofluoric acid and hydrogen peroxide, etching at room temperature for 30 minutes, and finally removing the remaining silver particles with nitric acid, washing and drying to obtain porous silicon. The porous silicon particles obtained by this method have a vertically arranged nanopore structure, uniform pore size, and large specific surface area.
[0040] Method 2: Use silica as a template and immerse it in silane gas; deposit silicon at 400°C to fill the pores of the silica template; etch the silica template with hydrofluoric acid to obtain porous silicon that is a reverse replica of the template. The porous silicon structure prepared by this method is highly controllable, and the structural characteristics of porous silicon can be adjusted by selecting silica templates with different pore sizes and morphologies.
[0041] Method 3: Mix hydrofluoric acid and ethanol in a volume ratio of 1:1; use a single crystal silicon wafer as the anode and a platinum wafer as the cathode, etch for 20 minutes at a current density of 10 mA / cm², wash with deionized water and dry to obtain porous silicon. This method is simple to operate, low in cost, and suitable for mass production.
[0042] Step 2: Mix the porous silicon with the phenolic resin and carbonize them in sections under an inert atmosphere. The specific operation is: fully mix the porous silicon prepared in step 1 with the phenolic resin in a mass ratio of 1:2, so that the phenolic resin is completely immersed in the pores of the porous silicon. Then, carbonize in sections under an inert atmosphere (such as argon or nitrogen): in the first stage, keep the temperature at 300°C for 2 hours to fully cross-link and solidify the phenolic resin; in the second stage, heat up to 800°C and keep the temperature for 5 hours to complete the carbonization process.
[0043] The low-temperature treatment in the first stage enables the phenolic resin to be fully crosslinked and cured, forming a stable three-dimensional network structure, preventing a large amount of gasification of the resin during the subsequent high-temperature carbonization process and resulting in carbon layer defects; the high-temperature carbonization in the second stage converts the resin near the surface of the silicon particles inside into hard carbon and the outer resin into soft carbon, forming a gradient carbon layer structure. This gradient carbon layer structure is due to the fact that during the carbonization process, the resin near the surface of the silicon particles is subjected to the catalytic action of the silicon surface and heat diffusion limitation, forming a more amorphous hard carbon structure; while the outer resin forms a partially graphitized soft carbon structure during the carbonization process.
[0044] Step 3: Ball-mill and mix the carbonized porous silicon with carbon nanotubes to form a three-dimensional conductive framework. The porous silicon particles coated with a gradient carbon layer obtained in Step 2 and carbon nanotubes are ball-milled and mixed according to a certain mass ratio (the mass ratio of carbon nanotubes is 5-10%) to make the carbon nanotubes uniformly dispersed and form an interconnected three-dimensional conductive network structure with the carbon-coated porous silicon particles. During the ball-milling process, part of the carbon nanotubes will insert into the surface of the carbon layer and form a firm bond with it, constructing a stable three-dimensional conductive framework.
[0045] In a preferred embodiment, the mass ratio of carbon nanotubes is 7%. This ratio can not only ensure the formation of a complete conductive network but also will not excessively occupy the mass of the electrode material and affect the overall energy density.
[0046] In another embodiment, the present invention also adds 1% LiF as an SEI film modifier after the end of Step 3 and performs prelithiation treatment to compensate for the irreversible capacity loss in the first cycle. As a component of the SEI film, LiF can significantly improve the stability of the SEI film and reduce the continuous consumption of the electrolyte; the prelithiation treatment compensates for the lithium consumed in forming the SEI film in the first cycle by introducing an appropriate amount of lithium into the material in advance, improving the first Coulombic efficiency of the battery.
[0047] The silicon-carbon negative electrode material and its preparation method of the present invention have the following remarkable beneficial effects: Beneficial effects of the porous silicon particle structure design: On the one hand, the porous structure provides abundant lithium-ion transmission channels, significantly improving the diffusion rate of lithium ions; on the other hand, the pores provide a buffer space for the volume expansion of the silicon material during the lithiation process, effectively alleviating the structural stress caused by the volume change and reducing the pulverization and cracking of the material.
[0048] Beneficial effects of the gradient carbon layer coating: The inner hard carbon is firmly combined with the silicon particles and has a high-strength structural support function; the outer soft carbon has good flexibility and conductivity and can adapt to the volume change of the silicon material without cracking. This gradient structure significantly improves the structural stability and conductivity of the carbon layer.
[0049] Beneficial effects of the three-dimensional conductive carbon nanotube framework: The three-dimensional conductive network formed by carbon nanotubes and carbon-coated porous silicon particles significantly improves the overall conductivity of the material and reduces the internal resistance of the electrode. At the same time, this three-dimensional framework structure can also provide mechanical support during the volume change process of silicon materials, maintain the integrity of the electrode structure, and prevent the active material from falling off the current collector.
[0050] Beneficial effects of the segmented carbonization process: Through the carefully designed segmented carbonization process, a gradient carbon layer with stable structure and strong bonding is formed on the surface of porous silicon, avoiding the carbon layer defects and peeling problems that are prone to occur in the traditional one-step carbonization process.
[0051] Beneficial effects of LiF addition and prelithiation treatment: The addition of LiF significantly improves the stability of the SEI film and reduces the continuous consumption of the electrolyte; the prelithiation treatment compensates for the irreversible capacity loss in the first cycle and improves the first Coulomb efficiency of the battery.
[0052] In summary, through the collaborative design of porous silicon particles, gradient carbon layers, and three-dimensional conductive carbon nanotube frameworks, the present invention successfully solves the problems of weak interfacial bonding, insufficient conductivity, and easy structural collapse existing in existing silicon-carbon anode materials. While maintaining the high specific capacity advantage of silicon-based anodes, this material significantly improves the cycle stability and rate performance, providing a new technical route for the development of high-performance lithium-ion battery anode materials.
[0053] Through comparative experiments, it is verified that, referring to Figure 1 , the first Coulomb efficiency of the silicon-carbon anode material of the present invention is 92% at a rate of 1C. Referring to Figure 2 , the capacity retention rate reaches 88% after 500 cycles at a rate of 0.5C. Referring to Figure 3 , XRD confirms that there is no free silicon oxide phase, showing excellent electrochemical performance and cycle stability.
[0054] The above has described the embodiments of the present application in detail with reference to the accompanying drawings. However, the present application is not limited to the above embodiments. Within the knowledge scope of those of ordinary skill in the art in the technical field, various changes can also be made without departing from the purpose of the present application.
Claims
1. A silicon-carbon anode material, characterized in that: It includes porous silicon particles, a gradient carbon layer, and carbon nanotubes. The gradient carbon layer coats the surface of the porous silicon particles. The gradient carbon layer includes an inner hard carbon layer and an outer soft carbon layer. The porous silicon particles and the carbon nanotubes are ball-milled and mixed to form a three-dimensional conductive framework.
2. The silicon-carbon anode material according to claim 1, characterized in that: The pore size of the porous silicon particles is 10 - 50 nm, and the porosity is 30 - 60%.
3. A method for preparing a silicon-carbon negative electrode material, which is used to prepare the silicon-carbon negative electrode material according to any one of claims 1 to 2, and is characterized in that, It includes the following steps: Step 1: Fabricate porous silicon. Step 2: Mix the porous silicon with phenolic resin and perform staged carbonization in an inert atmosphere. Step 3: Ball-mill and mix the carbonized porous silicon with carbon nanotubes to form a three-dimensional conductive framework.
4. The preparation method of the silicon-carbon negative electrode material according to claim 3, wherein: During the carbonization process in Step 2, keep it at 300 °C for 2 h in the first stage and at 800 °C for 5 h in the second stage.
5. The preparation method of the silicon-carbon anode material according to claim 3, wherein: In Step 3, the mass ratio of the carbon nanotubes is 5 - 10%.
6. The preparation method of the silicon-carbon anode material according to claim 3, characterized in that: In Step 2, the porous silicon and the phenolic resin are mixed in a mass ratio of 1:
2.
7. The preparation method of the silicon-carbon anode material according to claim 3, characterized in that, Fabricating porous silicon includes the following steps: Successively ultrasonically clean the single-crystalline silicon wafer with acetone, ethanol, and deionized water to remove surface contaminants. Sputter a 5 - 10 nm silver nanoparticle layer on the surface of the single-crystalline silicon wafer as a catalyst. Then immerse the single-crystalline silicon wafer in a mixed solution of hydrofluoric acid and hydrogen peroxide, etch at room temperature for 30 minutes, and finally remove the residual silver particles with nitric acid. After cleaning and drying, porous silicon is obtained.
8. The preparation method of the silicon-carbon anode material according to claim 3, characterized in that, Fabricating porous silicon includes the following steps: Use silicon dioxide as a template and immerse it in silane gas. Deposit silicon at 400 °C to fill the pores of the silicon dioxide template. Etch the silicon dioxide template with hydrofluoric acid to obtain porous silicon with an inverse replicated template.
9. The preparation method of the silicon-carbon anode material according to claim 3, characterized in that: Fabricating porous silicon includes the following steps: Mix hydrofluoric acid and ethanol in a volume ratio of 1:
1. Use the single-crystalline silicon wafer as the anode and the platinum wafer as the cathode, etch at a current density of 10 mA / cm² for 20 minutes, wash with deionized water and dry to obtain porous silicon.
10. The preparation method of the silicon-carbon anode material according to claim 3, characterized in that: Add 1% LiF as an SEI film modifier and perform prelithiation treatment to compensate for the first-cycle capacity loss.
Citation Information
Patent Citations
Preparation method of silicon-carbon negative electrode
CN118117072A
Silicon carbon composites comprising ultra low z
US20230219819A1
Cited By
Silicon-carbon negative electrode material with three-dimensional conductive network, preparation method of silicon-carbon negative electrode material and application of silicon-carbon negative electrode material in lithium battery
CN121282125A
Carbon nanotube reinforced silicon carbon core-shell negative electrode material and preparation method thereof
CN122158530A